The Measurement Of Employee Performance With A Human Resource Scorecard Methods: A Study Case in PDAM MEDAN - Siregar, Khairun Nissa; Sinulingga, Sukaria; Sembiring, Meilita Tryana (Jurnal Sistem Teknik Industri, 2022)
The success of an organization or company in carrying out tasks with the aim of realizing the company's vision, mission, and goals can be seen from the performance of its human resources. So far, PDAM Tirtanadi's employee performance measurement is still focused on the financial aspect and based on a preliminary questionnaire, employee performance is in the poor category. So that this research has the aim of designing indicators and measuring employee performance with the Human Resource Scorecard (HRSc) approach. HRSc is a performance measurement based on 4 perspectives, namely finance, employees, internal business processes, and growth. From the results of data collection and processing, 16 indicators and 18 key performance indicators (KPI) were obtained, so that by using the Likert scale method and questionnaire in each perspective, the measurement value was 3.385 with a less category.